DIMENSIONAL CALCULATION OF A MAST OF A MAST TYPE JIB CRANE FOR SLUDGE PUMPS HANDLING (Perner's Contacts, 2022)
This paper represents a continuation of the issue of the technical solution of the mast-type jib crane for handling sludge pumps. It is situated and used in building no. 900, block V2 of Jaslovské Bohunice nuclear power plant. It accounts for an optimization of the original, in operation damaged handling equipment with manual control of lift and rotation. The overload of the equipment has a negligible effect on the lifting force on a crank. It was ascertained that the lifting force still belongs to the recommended range of 120 N to 160 N for comfortable operation by one worker. Due to the fact that in the original design there is a complete absence of bearings in the rotating mechanism, it is the solution to this problem that is on the subject of the paper. The difficulties with lifting the pumps from sludge ambient, which occurred during the use of the mast jib crane, in a way opened the door to further design modifications to the original structure. As a solution, it is proposed to cancel the original construction of the carrier inserted into the support and replace it with a fixed mast on which the jib would rotate. In this way, on the one hand it would potentially be conceivable to increase the load capacity and thus solve the problem of lifting pumps attached to the bottom of a tank. On the other hand, it is also attainable to amplify the scope of action of this crane.